Pengaruh Pemakaian Klorin Terhadap Kadar Mangan (Mn) Dan Besi (Fe) Pada Post – Chlorinasi di PT Xyz - Rosmiati Rosmiati; Darry Christine Silowaty Purba; Adil Barus; Irwan Rachmiadji (JURNAL VOKASI TEKNIK, 2023)
The water of the Deli river used as raw water for PT. XYZ Deli Tua contains manganese and iron, which levels were quite high and exceeded the quality standard. The purposes of the research are to determine the effectiveness of caporite to reduce levels of manganese and iron to reach levels that meet the standards Minister of Health Regulation Number 492 of 2010. The sample used in this study was the water of the Deli river used as a source of raw water for PT. XYZ Medan water treatment plant (WTP) location in Deli Tua. Raw water was taken using a submersible water pump located at the bottom of the Deli river. The analytical method used as a reference manganese levels was based on 1- (2-Pyridylazo) -2-Naphthol PAN Method 1977, for determining iron levels was based on the FerroZine Rapid Liquid Method 1970, and for both methods using the Spectrophotometric method. The results showed that iron and manganese levels were quite high, exceeding the standards Minister of Health Regulation Number 492 of 2010 with a maximum standard of manganese level is 0.4 mg/L and a maximum standard of iron content is 0.3 mg/L. After adding a certain dose of chlorine to Deli river water in the Deli Tua WTP, it was found that chlorine effectively reduced Mn 66,6% and Fe 43,03% and meet the quality standards.